Composition of Stallion Seminal Plasma and Its Impact on Oxidative Stress Markers and Spermatozoa Quality - Tirpák, Filip; Halo, Marko; Tokárová, Katarína; Binkowski, Lukasz J; Vašíček, Jaromír; Svoradová, Andrea; Błaszczyk-Altman, Martyna; Kováčik, Anton; Tvrdá, Eva; Chrenek, Peter; Lukáč, Norbert; Massányi, Peter (Life (Basel, Switzerland), 2021)
The composition of seminal plasma of individual sires varies and so does the fertilizing ability. Micro and macro elements along with seminal enzymes, hormones, proteins, and lipids contained in seminal plasma are essential for the proper physiological function of spermatozoa. However, elevated levels against the normal physiological values, especially in the case of trace metals, result in the production of reactive oxygen species. The deficiency of antioxidants in the seminal plasma that could scavenge free radicals causes an impairment of spermatozoa quality. Ejaculates were obtained from 19 stallions. The fresh semen was analyzed to evaluate qualitative parameters of spermatozoa in terms of the motility, viability, and integrity of DNA. Separated seminal plasma underwent the assessment of the chemical and biochemical composition and RedOx markers. Based on the obtained concentrations of individual chemical elements, the correlation analysis suggested a negative impact of Cu in seminal plasma on the SOD, GPx, and LPO. Contrary, positive correlation was detected between FRAP and motility features. While Cu negatively correlated with sperm motion parameters, the adverse effect on viability was suggested for Cd. Our data suggest that seminal plasma has a potential due to its availability to become the potential biomarker of the reproductive health of farm animals.
Keywords: prooxidant activity; DNA; micro and macroelements; spermatozoa; horse; antioxidant activity